The Contribution of Self-Regulated Learning to the Academic Procrastination Behavior of Fast Track Students of the Master of Sports Education FIK UNNES - AnggieAP, Bambang Priyono, Ranu Baskora, Anggie Ade Pratiwi (Universitas Negeri Semarang, 2024)
This research aims to determine the contribution of self-regulated learning to the academic procrastination of fast track students at the Master of Sports Education, Faculty of Sports Science, UNNES. There is an influence of self-regulated learning on the academic procrastination of fast track students who are working on theses and theses so that the proposed hypothesis can be accepted, students who have high levels of self-regulated learning will have a high level of academic procrastination.This research uses a mixed method type of research. Mixed methods research design (mixed methods research design) is a procedure for collecting, analyzing and